Summability of alterations of convergent series - T. A. Keagy (International Journal of Mathematics and Mathematical Sciences)
The effect of splitting, rearrangement, and grouping series alterations on the summability of a convergent series by ℓ−ℓ and cs−cs matrix methods is studied. Conditions are determined that guarantee the existence of alterations that are transformed into divergent series and into series with preassigned sums.